Long-Term Trends in Screen Time Use Among Children and Adolescents: A Systematic Review Including Pre- and Post-COVID Periods - Mori, Yuko; Silwal, Sanju; Yunus; Wan Mohd Azam Wan Mohd; Sourander, Andre (SAGE Publications, 2026)
The rapid rise in internet access and smartphone use has significantly changed how children and adolescents engage in screen-based activities. To date, no systematic review has examined long-term trends in screen time use among children and adolescents that cover periods before and after the onset of the COVID-19 pandemic. This systematic review examined repeated cross-sectional studies to determine whether screen time use among children and adolescents changed over time. This systematic review was registered with PROSPERO (ID: CRD42021243869). The Web of Science, PubMed, Embase, and PsycINFO databases were searched to identify peer-reviewed studies that had been published in English, included data from at least two time points, and focused on children and adolescents between 0 and 19 years of age. The search was conducted without any restrictions on publication year. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Study quality was assessed using the Quality Assessment Tool for Studies with Diverse Designs. A narrative synthesis was conducted following the Synthesis Without Meta-analysis guidelines. This review identified 60 studies covering the period 1991-2022. The findings indicate that traditional TV watching declined while the use of computers and video games grew. Screen time increased significantly over the years, especially after the COVID-19 pandemic started. The studies reviewed varied in how they defined and measured screen time. The review underscores the importance of continued research and evidence-based policies to guide responsible technology use in the lives of young people.
Keywords: adolescent; child; repeated cross-sectional studies; screen time; systematic review; time-trend.